Between complexity and unfamiliarity: Preferences for soil-based ecosystem services - Bartosz Bartkowski; Julian Richard Massenberg; Nele Lienhoop (Helmholtz-Zentrum für Umweltforschung (UFZ), 2022)
Soils provide multiple benefits for human well-being, which are largely invisible to most beneficiaries. Here, we present the results of a discrete choice experiment into the preferences of Germans for soil-based ecosystem services. To tackle complexity and unfamiliarity of soils, we express soil-based ecosystem service attributes relative to the site-specific potential of soils to provide them. We investigate how knowledge about soils, awareness of their contributions to human well-being and experience with droughts and floods affect the preferences. We find substantial yet heterogeneous preferences for soil-based ecosystem services. Only some measures of familiarity exhibit significant effects on preferences.
Keywords: Q15; Q24; Q51; Q57; 330; Agriculture; Discrete choice experiment; Ecosystem services; Nonmarket valuation; Stated preferences; Soil functions; Willingness to pay